PENGARUH PROFITABILITAS, LIKUIDITAS DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK (STUDI PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2022) - Muhammad Hidayatullah; Muthia Harnida; Siti Mardah (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2023)
Indonesia is one of the largest countries in the world. The main source of state income comes from taxes. Therefore, the aim of this research is to find out how much influence of profitability, liquidity and leverage have on tax aggressiveness in mining sector companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The design of this research is a quantitative research. The research population used is all mining sector companies listed on the Indonesia Stock Exchange in 2020-2022 and the research sample was taken using purposive sampling, namely taking samples from the population based on certain criteria and the number were 11 companies in 2020-2022.This research uses descriptive statistical analysis, namely looking for the influence or relationship among variables. The measuring tool used in this research is SPSS 29 IBM Version. In this research, multiple linear analysis is used. The analytical methods used in this research are descriptive statistics, classical hypothesis testing, regression linear and hypothesis testing.From the research carried out, it was concluded that the profitability ratio is 0.008 <0.05, which means it has a significant influence. For the liquidity ratio, the value is 0.898 > 0.05, meaning that variable X2 has no effect on variable Y (Tax Aggressiveness). And the leverage ratio has a significance value of 0.169 > 0.05, which means it has no effect on tax aggressiveness. The results of the simultaneous test show that the three independent variables (X1, X2 and X3) have a joint influence on the dependent variable (Y). So the conclusion is that H1 is accepted, H2 and H3 are rejected and H4 is accepted.